Penerapan BIM untuk Efektivitas Sinkronisasi Elemen Utilitas pada Desain Perancangan Instalasi Poliklinik RS Dharma Husada Kediri - Az-zahra, Gissa Anjani Siti; Susanto, Ariadi (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2025)
This research evaluates the implementation of BIM in enhancing the synchronization of utility elements within the polyclinic installation design at Dharma Husada Kediri Hospital. The complex functional requirements of polyclinic spaces necessitate precise integration of plumbing elements (potable water, wastewater, medical gases) and ductwork for mechanical ventilation. The methodology includes a literature review on BIM’s role in coordinating utility elements, followed by an analysis of a polyclinic project in which 2D designs were converted into a 3D BIM model for simulation. Spatial and functional clashes between utility elements and the building structure were assessed using BIM, enabling early identification of potential conflicts among pipes, air ducts, beams, columns, and ceilings. The results demonstrate that BIM significantly improves software interoperability, facilitates interdisciplinary collaboration, and reduces the risk of design revisions during construction. Challenges encountered include discrepancies in modeling standards and variations in Levels of Detail (LOD), but the adoption of a collaborative platform effectively mitigates these obstacles. Therefore, BIM implementation proves to be a strategic approach for maximizingutility element coordination and can be replicated in other technically complex healthcare facility projects.